International Handbook of Self-Study of Teaching and Teacher Education Practices
XXIV, 1541 p.
Keywords: The International Handbook on Self-study of Teaching and Teacher Education Practices is of interest to teacher educators, teacher researchers and practitioner researchers. This volume: -offers an encyclopaedic review of the field of self-study; -examines in detail self-study in a range of teaching and teacher education contexts; -outlines a full understanding of the nature and development of self-study; -explores the development of a professional knowledge base for teaching through self-study; -purposefully represents self-study through research and practice; -illustrates examples of self-study in teaching and teacher education.